2022
DOI: 10.21608/asmj.2022.270241
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and Rhino-Orbital Mucormycosis: What's the Link?

Abstract: Background: COVID-19 associated mucormycosis (CAM) is an emerging disfiguring and fatal problem, which affects particularly patients with uncontrolled diabetes. The complex relationship between COVID-19 and mucormycosis is still mostly unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Regarding Gender of patients, our study found that more than half of cases (68.4) were females similar to Western India study Mishra et al (7) , and Ebrahim et al (8) study as 52.3% of studied patients were women, unlike most of previous studies which found that male gender represented the majority of cases (9)(10)(11) .…”
Section: Discussionsupporting
confidence: 82%
“…Regarding Gender of patients, our study found that more than half of cases (68.4) were females similar to Western India study Mishra et al (7) , and Ebrahim et al (8) study as 52.3% of studied patients were women, unlike most of previous studies which found that male gender represented the majority of cases (9)(10)(11) .…”
Section: Discussionsupporting
confidence: 82%